If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21x + -8 + -14x + 3 = 17x + -6 + -10x + 17 Reorder the terms: -8 + 3 + 21x + -14x = 17x + -6 + -10x + 17 Combine like terms: -8 + 3 = -5 -5 + 21x + -14x = 17x + -6 + -10x + 17 Combine like terms: 21x + -14x = 7x -5 + 7x = 17x + -6 + -10x + 17 Reorder the terms: -5 + 7x = -6 + 17 + 17x + -10x Combine like terms: -6 + 17 = 11 -5 + 7x = 11 + 17x + -10x Combine like terms: 17x + -10x = 7x -5 + 7x = 11 + 7x Add '-7x' to each side of the equation. -5 + 7x + -7x = 11 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 + 0 = 11 + 7x + -7x -5 = 11 + 7x + -7x Combine like terms: 7x + -7x = 0 -5 = 11 + 0 -5 = 11 Solving -5 = 11 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9a+14=4a+29 | | 15-4c=-10c+30 | | -6b=-14 | | 3a-2b=34 | | 4x^2-33x+55=-5x+10 | | 3b-6-9b-8= | | 2a+3b=26 | | 8a-15=2a-51 | | -3b-12= | | 12y^2-24y=4y | | 3xy+5yx= | | -2(u-3)(-u+9)=0 | | 3(x+2)-(x-3)=15 | | x+1+x+2-x+3=0 | | -2(u-3)(u+9)=0 | | 3x+5y-6= | | y=ln(7*x) | | -20x+10y-35= | | -9(v+4)+3v+7=6v+9 | | 3d-27+18= | | (3+y)(5y-7)=0 | | y=ln(7*y) | | 3w+9=16+w | | -4m-24= | | 2x^2+ax+b=0 | | 3u(u-8)(u-7)=0 | | -(c-3)=-2 | | F(x)=4x-3x | | 20+0.05x=10+0.07x | | 6x+4-2(x+1)=9x+6 | | 6(3s+8)=264 | | 9-9Ln(x+8)=-27 |